Long‐term L‐Triiodothyronine (T3) treatment in stable systolic heart failure patients: a randomised, double‐blind, cross‐over, placebo‐controlled intervention study. (17th December 2014) - Holmager, Pernille; Schmidt, Ulla; Mark, Peter; Andersen, Ulrik; Dominguez, Helena; Raymond, Ilan; Zerahn, Bo; Nygaard, Birte; Kistorp, Caroline; Faber, Jens
Summary: Background: Chronic heart failure (HF) is characterized by reduced serum T3 levels and increased activity of the T3 degrading enzyme deiodinase D3. This may result in an intracellular composition of the cardiomyocyte mimicking that of hypothyroidism. Short‐term T3‐administration to systolic HF patients might be beneficial. Question: Does long‐term treatment with T3 have a beneficial effect on cardiac function and neurohormonal activation in chronic systolic HF patients with serum T3 levels below 1·6 nmol/l? Design: A randomized, double‐blind, cross‐over, placebo‐controlled intervention study with oral T3 treatment twice daily for 3 months. The T3 dose was uptitrated to a final dose avoiding reduced TSH levels. Primary end‐point: Left‐ventricular ejection fraction (LVEF). Methods: Cardiac imaging was performed using multiple gated tomographic radionuclide ventriculography (MUGA‐SPECT). Neurohormonal stimulation was evaluated by plasma measurements of natriuretic peptides, aldosterone, renin, noradrenalin and copeptin levels. The patients were monitored for potential cardiac arrhythmias at the start of each treatment period. Results: Thirteen patients completed the protocol. Mean LVEF was 43%, range: 37–52 and serum T3 levels 1·4 nmol/l (0·9–1·6). The T3 dose was 20 μg per day (10–40). TSH levels did not change between groups, whereas serum T3 levels increased in the active arm. Cardiac function as measured by LVEF, end‐diastolic and end‐systolic volumes and cardiac output did not change during T3‐treatment and neither did the neurohormonal profile. There were no side‐effects in terms of cardiac arrhythmias and no change in resting heart rate. Conclusions: This study does not support the hypothesis that oral T3 treatment might be beneficial to patients with chronic, stable systolic HF with a modest degree of reduced LVEF and low‐normal serum T3 concentrations. The study included both functional studies of heart contractility as well as measures of the neurohormonal activation.